2021
DOI: 10.21037/atm-20-4849
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and anticoagulation strategies for left ventricular assist devices

Abstract: Left ventricular assist devices (LVAD) have revolutionized the management of advanced heart failure. However, complications rates remain high, among which hemorrhagic and thrombotic complications are the most important. Antiplatelet and anticoagulation strategies form a cornerstone of LVAD management and may directly affect LVAD complications. Concurrently, LVAD complications influence anticoagulation and anticoagulation management. A thorough understanding of device, patient, and management, including anticoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…HeartWare, the manufacturer for this patient’s ventricular assist device, specifically recommend aspirin 325 mg daily and warfarin with a goal INR of 2.0 to 3.0 for long-term anticoagulation [ 6 ]. Sufficient safety data for the use of DOACs is still lacking; therefore, they are not recommended for primary anticoagulation in patients with HVADs [ 3 ]. The presumed superiority of vitamin K antagonists may be explained by the underlying mechanism responsible for thrombus formation in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HeartWare, the manufacturer for this patient’s ventricular assist device, specifically recommend aspirin 325 mg daily and warfarin with a goal INR of 2.0 to 3.0 for long-term anticoagulation [ 6 ]. Sufficient safety data for the use of DOACs is still lacking; therefore, they are not recommended for primary anticoagulation in patients with HVADs [ 3 ]. The presumed superiority of vitamin K antagonists may be explained by the underlying mechanism responsible for thrombus formation in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis of 5 studies showed that patients with continuous-flow LVADs had a time in therapeutic range (TTR) of only 46.6% [ 2 ]. The many challenges with VKA led to an interest in using direct oral anticoagulants (DOAC) as an alternative option because of their ease of use and limited dietary interactions, despite the lack of solid safety data in LVAD patients [ 3 ]. Here, we present a case of a patient who developed an LVAD pump thrombosis while taking apixaban.…”
Section: Introductionmentioning
confidence: 99%
“…LMWH should be discontinued 12 h prior to surgery and UFH 6 h prior to surgery. 111 Preoperative temporary MCS, in particular VA‐ECMO, requires continuation of antithrombotic regimen with intravenous UFH. 109 …”
Section: Therapeutic Interventions In Cardiogenic Shock Requiring Specific Antithrombotic Regimensmentioning
confidence: 99%
“…Depending on the indication for anticoagulation, bridging with UFH and LWMH can be used to limit the time off anticoagulation prior to surgery. LMWH should be discontinued 12 h prior to surgery and UFH 6 h prior to surgery 111 . Preoperative temporary MCS, in particular VA‐ECMO, requires continuation of antithrombotic regimen with intravenous UFH 109 …”
Section: Therapeutic Interventions In Cardiogenic Shock Requiring Spe...mentioning
confidence: 99%
See 1 more Smart Citation